THE INFLUENCE OF DEMOCRATIC LEADERSHIP, ORGANIZATIONAL CULTURE, MOTIVATION AND WORK ENVIRONMENT ON PERFORMANCE AT THE OFFICE OF THE VILLAGE GOVERNMENT EMPOWERMENT OFFICE FOR POPULATION AND CIVIL REGISTRATION OF WEST NUSA TENGGARA PROVINCE - Hairil Hairil; Aftoni Sutanto; Abdul Choliq Hidayat (Jurnal Scientia, 2023)
The problem faced by the West Nusa Tenggara Dukcapil DPMPD Service is employee performance that could have been more optimal. Democratic Leadership, Organizational Culture, Organizational Motivation and Work Environment are suspected as factors that influence employee performance. This study aims to determine whether there is influence of Democratic Leadership, Organizational Culture, Organizational Motivation, and Work Environment on Employee Performance at the West Nusa Tenggara Dukcapil DPMPD Service. This type of research is quantitative research. The primary data used by researchers were taken from questionnaires that had been given to respondents. The population in this study were employees of the West Nusa Tenggara Dukcapil DPMPD Office, totaling 86 people. The number of employees used as samples is 80 employees with a census and using a saturated sample. The data obtained from the questionnaire. The data analysis technique uses multiple linear regression methods. The results of this study indicate that democratic leadership has a positive and significant effect on the performance of DPMPD Dukcapil Office Employees in West Nusa Tenggara Province. Organizational Culture has a positive and significant effect on the Performance of Social Service Employees of West Nusa Tenggara Province. Motivation has a positive and insignificant effect on the Performance of the West Nusa Tenggara Dukcapil DPMPD Office. The work environment has a positive and significant effect on the performance of employees of the Dukcapil Dukcapil Office of West Nusa Tenggara Province. This research also gives the result that on the variables of Leadership, Organizational Culture, Organizational Motivation and Work Environment.